A Study on Gender Roles in the Information Technology Profession and its Impact on Human Resources - Kraugusteeliana, Kraugusteeliana (PT. LITERASI SAINS NUSANTARA, 2023)
Information Technology (IT) is one of the fields that has an important role in the economic and social development of the world today. One important issue that continues to be of concern is the gender gap in the IT industry. This research aims to examine the role of gender in the IT profession and its influence on human resources. This research uses a qualitative methodology in the form of a literature review, which implies that the research will examine and explain data by utilising information and textual content from various sources. The study results show that gender roles in the Information Technology profession is an issue that is gaining increasing attention in the IT industry. Despite the increasing participation of women in IT careers, gender imbalance remains a significant problem. Factors such as gender stereotypes, inequality in opportunities, and differences in education contribute to this imbalance. As a result, unequal gender roles in the IT industry create inequalities in compensation and career opportunities, and also result in underrepresentation of women in leadership positions.